4 - Soins de santé primaires et médecine traditionnelle - à propos du développement des concepts de santé publique en Afrique *: Soins de Santé Primaires - une stratégie nouvelle - Wolfgang, BICHMANN (Africa Development, 1980)
* Une première version anglaise de cet article fut publiée dans Social Science and Medicine, Vol. 13 B, 1979, 175-182. Traditional health care has received attention lately in connec tion with WHO's «Primary Health Care»—strategy. This article tries to outline the significance of traditional medicine for the care of African populations. Within each society, differently conceptualized medical systems coexist. As Unshuld showed with his theory of professiona lization, nowhere does there exist a successful and complete integration of different medical systems. In the African context, apart from different forms of collaboration, we find a deliberate subordination of traditional healers and their knowledge under the dominating concept of cosmopo litan medicine. As Primary Health Care is thought to provide medical services accessible and acceptable to the local community, the author raises the question: why have there been real efforts to improve health services for rural populations on a nation-wide scale only in the seventies, although evidence has existed for more than ten years? The author advances the hypothesis that the economic function of a traditional rural sector in the reproduction of the labour force has been menaced by progressive degradation of living-standards there, and that the «basic needs»—development approach together with the Primary Health Care-strategy and the attempts at revaluation of traditional medicine, are aimed at preventing a collapse of the traditional rural sector. This would imply, that the emancipatory development approach, inherent in the original Primary Health Care strategy has been lost.